Nahwu Teaching Materials and the Development of Religious Character: Comparing Curriculum Design in Amtsilati and Mulakhkhash - Muhamad Saiful Mukminin; Muhammad Habibie Alfath; Tareq Alfraidi; Aqeel Ahmed (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
This study examines how the curriculum design of nahwu textbooks in Islamic education shapes students’ religious character, a dimension that has received limited attention in previous textbook comparison research. It analyses and compares the curriculum design of Amtsilati and Mulakhkhash Qawāʾid al-Lughah al-ʿArabiyyah and explores how their design features relate to the development of students’ religiosity. Using a qualitative descriptive–comparative approach, the study conducts document analysis of content materials, particularly learning examples and tables of contents. Data analysis involves selecting relevant text units, coding them according to Tyler’s four curriculum components, comparing the resulting profiles, and interpreting their implications for the intellectual, ritualistic, and consequential dimensions of religiosity based on Glock and Stark’s framework. The findings show that Amtsilati adopts a practical, drill‑based, spiral design that emphasises pattern repetition and accurate reading of kitab kuning, whereas Mulakhkhash employs a conceptual, systematically classified design centred on iʿrāb and syntactic analysis. Both enhance Arabic comprehension but nurture religious character differently: Amtsilati strengthens discipline, consistency, and confidence in worship‑related recitation, while Mulakhkhash fosters careful reasoning and intellectual responsibility. Conceptually, the study proposes a model that links textbook curriculum design to specific dimensions of religious character and offers practical insights for integrating practice‑oriented and concept‑oriented elements in nahwu instruction.